Investment in Agricultural Land Allocation Project by Investors in Bang Bua Thong District, Nonthaburi Province - Khlangkaew, Krongthong; srisatanon, pornpana; Tungjai, Sujidra; Vijchulata, Chanin (Journal of MCU Phetchaburi Review, 2023)
The objectives of this research were 1) to study the investors' factorsand investment decisions in the agricultural land projects of investors in Bang Bua Thong District. Nonthaburi Province 2) To compare the differences in investment decisions in the agricultural land projects 3) to study investment incentives affecting investment decisions in the agricultural land projects. The sample group was investors, totaling 385 people. The tool used to collect data was a questionnaire. Statistics used in data analysis were mean, standard deviation, t-test, F-test, and multiple regression analysis.The research results revealed that 1) Overall factors were at the highest level. Investment decisions in agricultural land projects of investors in Bang Bua Thong District. Nonthaburi Province Overall, the average was at the highest level. 2) Investors with different levels of education, status, and occupation had different decisions to invest in the agricultural land projects was statistically significant at 0.05. 3) Motivating investment factor 8 aspects were Agricultural land allocation projects, image, environment, Project features, way of life, Integrated communication, and facilities Affecting the decision to invest in the agricultural allocation land project and could explain the variation in investment decision variables in the agricultural land 77.00 percent